Tuberculosis and excess alcohol use in the United States, 1997-2012 - Volkmann, T; Moonan, P K; Miramontes, R; Oeltmann, J E (The international journal of tuberculosis and lung disease, 2015)
Excess alcohol use among tuberculosis (TB) patients complicates TB control strategies. To characterize the role of excess alcohol use in TB control, we describe the epidemiology of excess alcohol use and TB in the United States among those aged ⩾15 years. Using data reported to the National Tuberculosis Surveillance System, 1997-2012, we examined associations between excess alcohol use and TB treatment outcomes and markers for increased transmission (involvement in a local genotype cluster of cases) using multivariate logistic regression. We used Cox proportional hazards regression analysis to examine the relationship between excess alcohol use and the rate of conversion from positive to negative in sputum culture results. Excess alcohol use was documented for 31 207 (15.1%) of 207 307 patients. Prevalence of excess alcohol use was greater among male patients (20.6%) and US-born patients (24.6%). Excess alcohol use was associated with a positive sputum smear result (aOR 1.23, 95%CI 1.18-1.28) and death during treatment (vs. completion of treatment) (aOR 1.16, 95%CI 1.10-1.22). The rate of culture conversion was higher among patients without excess alcohol use (adjusted hazard ratio 1.20, 95%CI 1.18-1.23). Excess alcohol use was common among patients with TB, and was associated with TB transmission, lower rates of sputum culture conversion, and greater mortality.